Clinical aspects of envenomation caused by Tityus obscurus (Gervais, 1843) in two distinct regions of Para state, Brazilian Amazon basin: a prospective case series - Pardal, Pedro P. O.; Ishikawa, Edna A. Y.; Vieira, Jose L. F.; Coelho, Johne S.; Dorea, Regina C. C. [UNESP]; Abati, Paulo A. M.; Quiroga, Mariana M. M.; Chalkidis, Hipocrates M. (Biomed Central Ltd., 2014)
Background: Scorpion envenomations are a major public health problem in Brazil, whose most dangerous cases are attributable to the genus Tityus. This study was designed to compare the clinical and demographic features of envenomations by Tityus obscurus in two areas of the state of Para located in the Amazon basin. Were compared demographic findings, local and systemic signs and symptoms of human envenomations caused by T. obscurus that occurred in western and eastern areas of the state.Results: Forty-eight patients with confirmed envenomation by T. obscurus were evaluated from January 2008 to July 2011. Most of them came from the eastern region, where male and female patients were present in similar numbers, while males predominated in the west. Median age groups were also similar in both areas. Most scorpion stings took place during the day and occurred significantly more frequently on the upper limbs. The time between the sting and admission to the health center was less than three hours in both areas. Most eastern patients had local manifestations while in the west, systemic manifestations predominated. Local symptoms were similar in both areas, but systemic signs and symptoms were more common in the west. Symptoms frequently observed at the sting site were local and radiating pain, paresthesia, edema, erythema, sweating, piloerection and burning. The systemic manifestations were significantly higher in patients from the west. Futhermore, neurological symptoms such as general paresthesia, ataxia, dysarthria, myoclonus, dysmetria, and electric shock-like sensations throughout the body were reported only by patients from the west.Conclusion: The present study shows that two regions of Para state differ in the clinical manifestations and severity of confirmed envenomation by T. obscurus which suggests a toxicity variation resulting from the diversity of T. obscurus venom in different areas of the Brazilian Amazon basin, and that T. serrulatus antivenom can be successfully used against T. obscurus.
Keywords: Scorpionism; Tityus obscurus; Envenoming; Neurological symptoms; Brazilian Amazon